(untitled) (Journal of the College of Education for Women, 2019)
Iraqi-Saudi Relations have witnessed a state of rapprochement over decades. However, this rapprochement was temporary and could not overcome the differences that formed the core of Iraqi-Saudi relations after 2003, relations between Iraq and Saudi Arabia deteriorated with the Iraqi governments that followed the rule of Iraq after 2003, especially the government of Nuri Al-Maliki in which relations reached the end of mutual accusations between the two parties. In order to promote the relationship between the two countries, a culture of moderation has to be propagated especially in the field of religion and the religious institution should be encouraged to open up to other sects and to recognize all sects as prelude to combating the culture of extremism and atonement and eliminating terrorist organization that take cover of religion such as Al-Qaeda and other terrorist organizations. The Iraqi and Saudi governments should also strive to build excellent relations in which communications is the cornerstone for them. As well as the development of economic relations in a manner that rises to the level of responsibility between the two countries.